Clinical Research of Pulmonary Langerhans Cell Histiocytosis in Children - Dong Wang; Lei Cui; Zhi-Gang Li; Li Zhang; Hong-Yun Lian; Hong-Hao Ma; Yun-Ze Zhao; Xiao-Xi Zhao; Tian-You Wang; Rui Zhang (Chinese Medical Journal, 2018)
Background: Pulmonary Langerhans cell histiocytosis (PLCH) is an interstitial primary pulmonary disease, characterized by Langerhans cell proliferation. It is easily misdiagnosed in children. This study aimed to characterize the clinical manifestations and features of PLCH by retrospective analysis. Methods: A retrospective analysis was performed in 117 PLCH patients out of 338 LCH patients who were admitted in our center from November 2006 to October 2013. Variables between two groups were compared by Mann-Whitney U-test and Chi-square test. Kaplan-Meier curves were constructed to compare the survival rates and Cox regression to evaluate the effect of risk factors. Results: The median age of PLCH group was significantly lower than that of non-PLCH group (18.63 months vs. 43.4 months, P < 0.001). All PLCH children had other organ involvement and only 11 cases (9.4%) had respiratory symptoms. The most common radiologic finding was cystic lesions (29 cases, 24.8%). Pulmonary function abnormalities were dominated by obstructive ventilatory dysfunction (63 cases, 82.9%). The 5-year overall survival (OS) of PLCH children was 93.6% ± 2.3% and the event-free survival (EFS) was 55.7% ± 5.2%. Among the 38 cases with progressed or relapsed disease, five cases (13.2%) were due to progression or recurrence of lung damage. The 5-year OS of PLCH children with “risk organ” involvement was significantly lower than those without “risk organ” involvement (86.0% ± 4.9% vs. 100%, χ2 = 8.793, P = 0.003). The difference of EFS between two groups was also significant (43.7% ± 7.7% vs. 66.3% ± 6.5%, χ2 = 5.399, P = 0.020). The “risk organ” involvement had a significant impact on survival (hazard ratio = 1.9, P = 0.039). Conclusions: PLCH mainly occurs in young children, and only a small percentage of patients have respiratory symptoms. They generally have other organ involvement. Most of PLCH children have a good prognosis and most lung lesions could have improved or stabilized. Management of “risk organ” involvement is the key point to improving EFS.